The Dewatering of the Fucino Lake Did Not Promote the M7.1 1915 Fucino Earthquake: Insights From Numerical Simulations. Issue 8 (17th August 2018) - Cucci, L.; Currenti, G.; Palano, M.; Tertulliani, A.
Plain Language Summary: The powerful M 7.1 earthquake that devastated the Fucino Basin (Central Italy) in 1915 occurred only 38 years after the complete man‐induced dewatering of the largest lake of peninsular Italy, which formerly occupied the basin. Hence, we investigate on a possible relationship between the dewatering of the lake and the occurrence of the 1915 earthquake. We find that the stress changes originated by the Fucino Lake dewatering represent the main factor of perturbation in the area prior to 1915; however, such a dewatering process may have only slightly (a couple of years) delayed the occurrence of the strong rupture of the 1915 earthquake. Our work confirms the possibility that human activities can induce a temporal delay in the occurrence of future earthquakes.